Berberine attenuates TNBS-induced colitis in mice by improving the intestinal microbiota - Li, Chao; Yin, Xinxin; Xie, Changpeng; Zeng, Jin; Song, Chuan; Yang, Guibin; Zhang, Jinglei; Chen, Siai; Wei, Panjian; Wang, Ziyu; Gu, Meng; Li, Wei; et al. (Frontiers in Microbiology, 2024)
Objective To investigate the effects of berberine (BBR) as a treatment on intestinal microecological alterations and enteritis in mice produced by TNBS. Methods There were seven mice per group: seven in the healthy group (Ctrl), seven in the TNBS-induced enteritis group (TNBS), and seven in the berberine treatment group (BBR). The mice were weighed, slaughtered after 7 days, and subjected to high-throughput intestinal microecological analysis by Illumina, as well as haematological detection and imaging evaluation of colon pathology. Results The alterations in colon length, immune cell subpopulations, inflammatory factors, and intestinal microecology of mice induced by BBR were refined using a battery of experiments and observations. According to intestinal microecological studies, BBR can increase the number of bacteria, including Lactobacillus, Verrucomicrobia, Bacteroides, and Akkermansia muciniphila. Conclusion BBR has a therapeutic effect on TNBS-induced colitis in mice, which is associated with modifications in immune cell subpopulations and intestinal microecology. It also offers a viable approach as a prospective probiotic (like Akkermansia muciniphila) to IBD therapy in clinical settings.